2011
DOI: 10.1080/10495398.2011.552031
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Gene Expression Associated with Increased Marbling in Beef Cattle

Abstract: Selection of breeding stock is a crucial step in any breeding program, therefore the methodology for animal evaluation has evolved rapidly and in recent decades has incorporated the use of molecular markers. Several multinational companies have made available to producers commercial tests based on these technologies, which allow assessing the predisposition of animals to express a specific phenotype. However, some doubts have begun to arise about negative effects of improper use of molecular markers, these are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 15 publications
2
17
0
3
Order By: Relevance
“…Hence, the relationship of NR2F2 expression with fat content in cattle needs further study and discussion. Studies have shown that MXRA8 expression level is associated with increased marbling in beef cattle [33]. In addition, LPIN1 is a candidate gene for fat deposition in pigs [34].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the relationship of NR2F2 expression with fat content in cattle needs further study and discussion. Studies have shown that MXRA8 expression level is associated with increased marbling in beef cattle [33]. In addition, LPIN1 is a candidate gene for fat deposition in pigs [34].…”
Section: Discussionmentioning
confidence: 99%
“…However, to date a link between MXRA8 and lipid metabolism has been documented by only one publication. MXRA8 was indeed shown as an upregulated gene when bovines with high carcass adiposity and marbling were compared with slightly adipose bovines (16). The heat shock protein HSP 90-alpha (HSP90AA1) is related to muscular physiology by regulating transforming growth factor ␤ (TGF᎑␤), by folding the myosin motor domain and organizing the filament structure of myofibers (22).…”
Section: Transcriptional Signature Related To Lipid Metabolismmentioning
confidence: 99%
“…Meat tenderness와 연관된 대표적인 유전자는 CAPN1(calciumactivated neutral protease 1)과 CAST(calpastatin) 등 이 있으며 (Casas et al, 2006;Morris et al, 2006;Nonneman et al, 1999;Oh et al, 2010;Schenkel et al, 2006), marbling score의 경우 DGAT1(diacylglycerol O-acyltransferase 1), TG(thyroglobulin) 그리고 LEP(leptin) Thaller et al, 2003) 상업적으로도 이용이 되고 있는 유 전자들이다. 이 외에도 육질형질과 관련된 많은 유전자들 이 보고되고 있으며 이를 활용한 육종 기술개발 연구가 진 행되고 있다 (Clark et al, 2011;Jiao et al, 2010;Lee et al, 2008;Marques et al, 2009;Wu et al, 2005).…”
Section: 서 론unclassified